Communication between Tandem cAMP Binding Domains in the Regulatory Subunit of Protein Kinase A-Iα as Revealed by Domain-silencing Mutations - McNicholl, E. Tyler (American Society for Biochemistry and Molecular Biology, 2010)
Protein kinase A (PKA) is the main receptor for the universal cAMP second messenger. PKA is a tetramer with two catalytic (C) and two regulatory (R) subunits, each including two tandem cAMP binding domains, i.e. CBD-A and -B. Structural investigations of RIα have revealed that although CBD-A plays a pivotal role in the cAMP-dependent inhibition of C, the main function of CBD-B is to regulate the access of cAMP to site A. To further understand the mechanism underlying the cross-talk between CBD-A and -B, we report here the NMR investigation of a construct of R, RIα-(119–379), which unlike previous fragments characterized by NMR, spans in full both CBDs. Our NMR studies were also extended to two mutants, R209K and the corresponding R333K, which severely reduce the affinity of cAMP for CBD-A and -B, respectively. The comparative NMR analysis of wild-type RIα-(119–379) and of the two domain silencing mutations has led to the definition at an unprecedented level of detail of both intra- and interdomain allosteric networks, revealing several striking differences between the two CBDs. First, the two domains, although homologous in sequence and structure, exhibit remarkably different responses to the R/K mutations especially at the β2-3 allosteric “hot spot.” Second, although the two CBDs are reciprocally coupled at the level of local unfolding of the hinge, the A-to-B and B-to-A pathways are dramatically asymmetrical at the level of global unfolding. Such an asymmetric interdomain cross-talk ensures efficiency and robustness in both the activation and de-activation of PKA.